Bifid Shape Is Intrinsic to Bifidobacterium adolescentis - Dhanashree,; Rajashekharan, Sharika; Krishnaswamy, Balamurugan; Kammara, Rajagopal (Frontiers in Microbiology, 2017)
Although the genus Bifidobacterium was originally named for its bifid morphology, not all bifidobacterial species have a similar structure and very few of them adopt a bifid shape under stress conditions. Some adopt a bifid shape after 36 h of growth, before which they retain the rod form. Most Bifidobacterial species are anaerobic and rod-shaped, whereas after the first generation, they become microaerophilic or aerophilic. CaCl2 (treatment of B. animalis) signaling triggered a change from the rod shape to the bifid shape and bifid to rod in B. adolescentis. The exposure of B. adolescentis and other bifidobacterial species to various conditions, such as different pHs, temperatures, medium components, in vivo growth in Caenorhabditis elegans, and subculture, did not affect their diverse morphologies. Extensive scanning electron microscopy studies suggested that the bifid shape of B. adolescentis are maintained irrespective of the conditions, so this morphology is intrinsic to B. adolescentis.